2022
DOI: 10.3389/fphys.2022.995004
|View full text |Cite
|
Sign up to set email alerts
|

Function of Vitellogenin receptor gene in reproductive regulation of Zeugodacus cucurbitae (Coquillett) after short-term high-temperature treatment

Abstract: Climate change has increased the frequency of extreme heat events. Zeugodacus cucurbitae (Coquillett) is an important tropical pest that typically changes its reproductive strategies in response to extremely high temperatures. Newly emerged adults of three consecutive generations (F1, F2, and F3) of Z. cucurbitae (Coquillett) were exposed to 25°C, 33°C, 37°C, 41°C, and 45°C treatments for 1 h to clarify the effects of short-term high temperatures on its reproduction. The influence of these temperatures on repr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Following a previous study (Lian et al, 2022a), siRNA for the ZcVgR gene was synthesised by Tsingke Biotech (Shanghai, China) with a positive strand of 5' CGAUGUCGAGGAUGUGUUATT 3' and an antisense strand of 5' UAACACAUCCUCGACAUCGTT 3'.…”
Section: Synthesis and Design Of Sirnamentioning
confidence: 99%
See 1 more Smart Citation
“…Following a previous study (Lian et al, 2022a), siRNA for the ZcVgR gene was synthesised by Tsingke Biotech (Shanghai, China) with a positive strand of 5' CGAUGUCGAGGAUGUGUUATT 3' and an antisense strand of 5' UAACACAUCCUCGACAUCGTT 3'.…”
Section: Synthesis and Design Of Sirnamentioning
confidence: 99%
“…The relative expression of the ZcVgR gene was measured in newly emerged female Z. cucurbitae treated at 33°C, 37°C, 41°C and 45°C for 1 h. It was concluded that short-term high temperature treatment drove the downregulation of the ZcVgR gene, and the expression of the ZcVgR gene increased progressively with increasing number of days, and it increased rapidly from 5 d to reach the peak at 7 d (Lian et al, 2022b). To investigate the function of the ZcVgR gene in female Z. cucurbitae mediated by short-term high temperature, newly emerged females were treated at 45°C for 1 h, and then injected with siRNA to silence the ZcVgR gene at 5 d of age, and the egg number and lifespan of females were signi cantly reduced (Lian et al, 2022a), suggesting that the ZcVgR gene is involved in the regulation of reproduction and lifespan in females mediated by short-term high temperature. However, how does the ZcVgR gene regulate short-term high temperature-mediated reproduction and lifespan in female Z. cucurbitae?…”
Section: Introductionmentioning
confidence: 99%
“…VgR, in concert with Vg, is involved in a range of physiological and behavioral activities in insects ( Lian et al, 2022b ). Our previous research showed that the reproductive ability and ovarian development rate of Z. cucurbitae were significantly decreased after interference with the VgR gene of 5-day-old females ( Lian et al, 2022a ). In addition, we found that interference with the VgR gene impacted the lifespan of female Z. cucurbitae ; however, the mechanism of that effect was unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In Z. cucurbitae, the injection or ingestion of gene-specific dsRNAs successfully suppressed the target gene expression in larvae and adults, leading to developmental defects and mortality. For instance, the knockdown of vitellogenin genes significantly reduced its fecundity and caused ovarian defects (Chen et al, 2022;Li et al, 2021;Lian et al, 2022), while the knockdown of imaginal disc growth factors (IDGF6) caused wing malformation, the knockdown of the tyrosineprotein kinase-like tok gene (Tpk-Tok) caused a black and distorted body and major larval mortality and the knockdown of Argonaute1 (Ago1) and Gawky affected ovarian development and pigmentation (Ahmad et al, 2021(Ahmad et al, , 2023aJamil et al, 2022). To further develop efficient RNAi-based pest control strategies for Z. cucurbitae achieving very high larval mortality (the most destructive stage), it is important to test new gene candidates, which could later be targeted in cosilencing approaches (Ahmad et al, 2023b).…”
Section: Introductionmentioning
confidence: 99%